Cenozoic evolution of the steppe-desert biome in Central Asia - Barbolini, Natasha; Woutersen, A.; Dupont-Nivet, G.; Silvestro, D.; Tardif, D.; Coster, P. M. C.; Meijer, N.; Chang, C.; Zhang, H.-X.; Licht, A.; Rydin, C.; Koutsodendris, Andreas; et al. (Science advances, 2020)
The origins and development of the arid and highly seasonal steppe-desert biome in Central Asia, the largest of its kind in the world, remain largely unconstrained by existing records. It is unclear how Cenozoic climatic, geological, and biological forces, acting at diverse spatial and temporal scales, shaped Central Asian ecosystems through time. Our synthesis shows that the Central Asian steppe-desert has existed since at least Eocene times but experienced no less than two regime shifts, one at the Eocene-Oligocene Transition and one in the mid-Miocene. These shifts separated three successive “stable states,” each characterized by unique floral and faunal structures. Past responses to disturbance in the Asian steppe-desert imply that modern ecosystems are unlikely to recover their present structures and diversity if forced into a new regime. This is of concern for Asian steppes today, which are being modified for human use and lost to desertification at unprecedented rates. - The steppe-desert is much older than previously thought, but has evolved substantially from the Paleogene to the present. - The steppe-desert is much older than previously thought, but has evolved substantially from the Paleogene to the present.